A critical review on the rationality of popular failure criteria for composites - Li, Shuguang; Sitnikova, Elena (Elsevier, 2018)
Popular failure criteria for fibre reinforced composites are subjected to critical scrutiny on their rationality. The rationality of a theory is about the mathematical and physical logic underlying the theory, rather than the closeness of their results in comparison with experimental data. Seeking for close comparisons with a set of experimental data before obtaining a basic level of rationality is not a scientific attitude, although the practice is becoming the norm in the community of science and engineering. A theory lacking of rationality can never be a sound one no matter how closely it compares with experimental data in one respect or another, since a good comparison in one respect comes at a price of poor agreement in some other respects usually, either unknown for the time being or hidden deliberately. The objective of this paper to raise the awareness of rationality, or the lack of it, in existing theories so that the users will be warned to exercise their judgement on the applicability of these theories before employing them in future. It should also help the researchers avoid incorporating illogical considerations into the formulations of the new theories they are developing.